The Influence of Aluminium Concentration on the Hydration of ZSM-5-Type Zeolites in Aqueous Suspensions - V.V. Turov; V.V. Brei; K.N. Khomenko; R. Leboda (Adsorption Science & Technology)
The 1 H NMR spectral technique has been applied to the study of samples of ZSM-5-type zeolites. These samples were synthesized using the template procedure and possessed various aluminium concentrations in their crystal lattice. The characteristics of the adsorbed water layers and the values of the free surface energy of the adsorbents were determined. It was established that, for aqueous suspensions of zeolites, the highest concentration of water in the pores was characteristic of the sample containing the lowest amount of aluminium. It was suggested that the amount of water in the pores is determined not so much by the concentration of primary adsorption sites as by the conditions under which the development of water clusters occurs as well as by the competing sorption of water and ambient air.